Utilization of kappa-carrageenan for quality improvement of "Pan De Sal" - Siccion, Marivic P.; Dumelod, Benelyn Domingo (1994.)
This study was conducted with the main objective of improving the qualities of "pan de sal" particularly volume and texture (mouthfeel and grain or cell structure). A preliminary study was conducted to acquire the needed baking skills to produce desirable "pan de sal." Phase I was done to determine the best method of incorporating kappa-carrageenan. Two methods were evaluated: addition in the slurry, and in the flour. Sensory results revealed that the former was better. Phase II was divided into two sub-phases. Phase IIA determined the optimum level of kappa-carrageenan while Phase IIB dealt with the standardization of the formulation and process for "pan de sal" using the optimum level. Phase IIA results showed that 0.075% was the optimum level of kappa-carrageenan which improved bread quality, increased the production yield and lowered the cost. Phase IIB resulted to a standardized formulation and process which produced bread rated as having a soft mouthfeel, uniform cell structure, sweet and salty taste, golden brown crust color and with an overall acceptability corresponding to "like very much." The standard production yield was 25 pieces per 500 g batch recipe costing P0.34 a piece. Phase III translated production from laboratory to pilot scale. The products showed the same attributes as in Phase IIB except for the crust color which was pale yellow. The two-kilogram batch yielded 95 pieces which was 7 pieces more than the former yield in the original recipe. Based on the experimental results, the 0.75% level of kappa-carrageenan has improved the bread qualities of "pan de sal," increased production yield, and decreased cost per piece.
Thesis (BSFT)--University of the Philippines.
Keywords: Chondrus crispus; Bread